Pembelajaran Unggah-Ungguhing Bahasa Jawa sebagai Pendidikan Karakter pada Siswa Kelas 5 SD Muhammadiyah PK Boyolali - Pratiwi, Rima Yunika; , Drs. H. Mulyadi Sri Kamulyan., S.H., M.Pd (2017)
This researchis aimed to determines: 1) The process of learning implementation of the unggah-ungguhing Javanese language as character education in 5th grade of SD Muhammadiyah PK Boyolali, 2) The obstacles faced by teachers in the process of learning implementation of the unggah-ungguhing Javanese language as character education in 5th grade of SD Muhammadiyah PK Boyolali, and 3) The solutions of the obstacles of the unggah-ungguhing Javanese language as character education in 5th grade of SD Muhammadiyah PK Boyolali. This research is a qualitative research with qualitative descriptive design. The informants of this reaserch are the Javanese teacher, the students in the 5th grade of SD Muhammadiyah PK Boyolali and the teachers of SD Muhammadiyah PK Boyolali. The data collections techniques of this research are interviews, observation, and literature as well as documentation to supporting this research. The data were analyzed by data reduction, display data and conclusions/verification. Triangulation is used to check the validity of the data. The results showed that the process of learning implementation of the unggah-ungguhing Javanese language as character education in 5th grade of SD Muhammadiyah PK Boyolali is good, but it has found the obstacles of the process, especially in the application of the Javanese language in their daily life, so the solutions to overcome the obstacles are always teaching and reminding the students about unggah-ungguhing Javanese language as character education, and should be interference from family and schools to facilitate the students in using the unggah-ungguh and undha-ushuk.